2019
DOI: 10.1002/bdr2.1537
|View full text |Cite
|
Sign up to set email alerts
|

Using Telehealth to address disparities in cognitive, language, and emotion regulation problems in young children: A case illustration using the INvesT model

Abstract: Over the past decade, there has been a rise in the prevalence of developmental dis-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Only one study reported separate demographics for the 0–3 age range (Tariq et al, 2019), with M age = 30 months (60% male). Three of the remaining studies did not report the mean age (Ciccia, Whitford, Krumm, & McNeal, 2011; Duda, Daniels, & Wall, 2016; Maleka, Van Der Line, Page Glascoe, & Swanepoel, 2016), whereas the other three studies reported only the mean age and gender breakdown of all participants, including those who were over 3 years old (Obeid, Beekman, Roizen, Ciccia, & Short, 2019; Smith et al, 2017; Tariq et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only one study reported separate demographics for the 0–3 age range (Tariq et al, 2019), with M age = 30 months (60% male). Three of the remaining studies did not report the mean age (Ciccia, Whitford, Krumm, & McNeal, 2011; Duda, Daniels, & Wall, 2016; Maleka, Van Der Line, Page Glascoe, & Swanepoel, 2016), whereas the other three studies reported only the mean age and gender breakdown of all participants, including those who were over 3 years old (Obeid, Beekman, Roizen, Ciccia, & Short, 2019; Smith et al, 2017; Tariq et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of ethnicity, four studies reported a breakdown of ethnicities. Maleka et al (2016) and Obeid et al (2019) examined a majority of African or African American participants (>93%), whereas Smith et al (2017) examined a majority of Caucasian (41%) and Hispanic (43%) participants. Tariq et al (2019) examined only Bangladeshi participants, who were located in a primarily urban location (92.7%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These are times of great change and, in these moments, the opportunity to develop new and valuable patterns of care should be seized 41 . Telemedicine in pediatric clinics has already been trialed 42 and not only facilitates increased access to specialist review for geographically dispersed patients 43 but also offers the additional insights of reviewing children in their own homes and with their families. Why not adapt similar methods for the long‐term follow‐up of MC pregnancies by central fetal therapy centers?…”
Section: Introductionmentioning
confidence: 99%